Policy initiative to improve access to CSC Finance for Public and Private Sector Investment - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Holzer, Manuel; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This policy document highlights the results of the Cost-Benefit Analysis (CBA) from the pilots which forms the basis for the development of Climate Smart Cocoa (CSC) Finance packages. It gives a clear pathway towards giving more access for women and youth to CSC finance which will ultimately lead to CSC adoption.